Educational framework for coaches on injury prevention in adolescent team sports - Gouws, C.; Millard, L.; Naude, A.; Meyer, J.-W.; Shaw, B. S.; Shaw, I. (Asian Journal of Sports Medicine, 2020)
Background: Millions of South African youths participate in team sports, with netball and rugby being two of the largest worldwide. This increased participation and professionalism has resulted in an increase in the number of musculoskeletal injuries.